Application of Word of Mouth (WOM), Information Quality, and Brand Trust in Increasing Customer Loyalty of Rice Seeds of Inpari 32 Variety - Murning; Abdul Wahib Muhaimin; Silvana Maulidah (Postgraduate, University of Mataram, 2024)
The purpose of this study was to determine the effect of Word of Mouth (WOM), information quality, and brand trust in increasing customer loyalty of rice seed varieties inpari 32. This research was conducted at Gapoktan Rahayu, Temu Village, Kanor District, Bojonegoro Regency. It is a research that adopts a quantitative approach. In data analysis, this study uses the PLS-SEM (Partial Least Square-Structural Equation Modelling) method to evaluate the impact of Word of Mouth (WOM), Information Quality and Brand Trust variables on Customer Loyalty on Inpari 32 variety products. Based on the results of the study, it was obtained that the first hypothesis to the fifth hypothesis all had a significant effect on increasing customer loyalty for Inpari 32 variety rice seeds. Word Of Mouth (WOM) has a crucial role because it is able to direct, recommend, and provide positive information about the product. Information Quality provides information to customers that the product meets their needs completely and accurately. Brand Trust makes consumers believe in the quality and reliability of the product. Customer loyalty is reflected in their desire to continue to buy products, recommend to others, and are willing to pay more and wait for the availability of goods.